The Effect of Barman's Model on acquiring the Concepts of Fiqh of Worship among Students of Departments of Qur'anic Sciences (Journal of the College of Education for Women, 2023)
The current research seeks to identify the impact of Barman's model on acquisition of the concepts of jurisprudence of worship among students of the departments of Qur'anic sciences. To achieve the research objectives, the researcher relied on the experimental method through a design with partial control by relying on two experimental groups receiving teaching by using the Barman model and a control group receives teaching through the normal method. After applying the experiment, the study reached the following results: Students of the Department of Qur’anic Sciences in general need educational programs linked to the curriculum and built on scientific foundations, according to their needs and problems (psychological, cognitive, and social), as well as their age or academic stage. The program followed in our colleges, according to the results of the research, is one of the methods that cannot be dispensed with and can give good results if it is employed in a modern manner through pre-prepared teaching plans that employ all the diverse teaching capabilities in the educational situation.